Analysis of the Relationship between Environmental Sanitation and the Incidence of Diarrhea in Toddlers at the Khairani Siregar BPM Clinic, Batu VI Housing Complex, Simalungun Regency - Friani, Sri Rahma; Purba, Yeni Trisna; Riza, Nor (International Journal of Public Health Excellence (IJPHE), 2024)
Diarrhea is still a health problem and a cause of death in toddlers. Poor environmental sanitation can affect the high incidence of diarrhea. According to the World Health Organization (WHO) in 2021 diarrhea is the second leading disease that causes death in toddlers and causes 525,000 toddlers to die each year. The research design used was correlational analytic with a cross-sectional approach. The population in this study were mothers who had toddlers who experienced diarrhea at BPM Khairani Perumnas Batu VI, Simalungun Regency, totaling 38 people. The sampling technique was total sampling. Data collection was carried out by filling out questionnaires and data analysis using univariate analysis and bivariate analysis with the Chi-Square statistical test. From the results of the study, it was obtained based on drinking water sources that the Chi-Square test results were obtained with a P value of 0.001 (<0.05). Based on the ownership of toilets, the Chi Square test results showed a p-value = 0.002 (≤ 0.05) and based on the type of house floor, the p-value = 0.002 (≤ 0.05). It can be concluded that there is a significant relationship between drinking water sources, family toilet ownership and type of house floor with the incidence of diarrhea in toddlers. It is hoped that health workers will further maximize health programs, one of which is regarding increasing public knowledge, especially mothers who have toddlers, about environmental sanitation to prevent the incidence of diarrhea in toddlers.